2021
DOI: 10.3390/cancers13215319
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Bone Marrow Microenvironment-Driven Mechanisms of Drug Resistance in Acute Myeloid Leukemia: Tangle or Chance?

Abstract: Acute myeloid leukemia (AML) has been considered for a long time exclusively driven by critical mutations in hematopoietic stem cells. Recently, the contribution of further players, such as stromal and immune bone marrow (BM) microenvironment components, to AML onset and progression has been pointed out. In particular, mesenchymal stromal cells (MSCs) steadily remodel the leukemic niche, not only favoring leukemic cell growth and development but also tuning their responsiveness to treatments. The list of mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 211 publications
1
11
0
Order By: Relevance
“…Recently, increasing evidence has indicated that MSCs become activated during drug treatment and secrete factors that protect tumor cells against a range of chemotherapeutics ( 24 , 25 ). MSCs derived from adipose tissues are involved in a gradual loss of the repair capacity of oxidative DNA damage and accumulation of DNA damage, which are associated with drug resistance ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidence has indicated that MSCs become activated during drug treatment and secrete factors that protect tumor cells against a range of chemotherapeutics ( 24 , 25 ). MSCs derived from adipose tissues are involved in a gradual loss of the repair capacity of oxidative DNA damage and accumulation of DNA damage, which are associated with drug resistance ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting its CXCR4 receptor (by antagonist or neutralizing antibodies) reduced AML burden and disease progression without affecting HSC engraftment [ 138 ]. Not all of the survival mechanisms induced by MSCs have been totally elucidated, but it is suggested that common adhesion downstream effectors are responsible and may be effective targets of treatment [ 139 ]. AML-derived MSCs showed diminished cell growth and CFU-F, and altered morphology [ 77 , 140 , 141 , 142 ].…”
Section: The Effect Of Leukemic Cells On Mesenchymal Stem Cell Proper...mentioning
confidence: 99%
“…More recently, the role of EVs was also included in the list of mechanisms contributing to AML cells’ protection [ 273 ]. EVs from MSCs and AML cells can reshape the BM microenvironment, and it has been demonstrated that EVs are increased in AML patients’ plasma, even after chemotherapy and remission [ 139 , 274 ]. RNAs, miRNAs and transcripts of FLT3-ITD, nucleophosmin-1 (NPM1), IGF-IR, CXCR4 and MMP9 present within EVs, alter stromal cells, and have important roles in AML treatment and prognosis [ 275 ].…”
Section: Msc Roles In Drug Resistancementioning
confidence: 99%
“…What is known, however, is that the microenvironment characteristics are highly dependent on the dynamics of the niche cell populations (turnover kinetics, physiological state, mutation accumulation rate, among others) [17]. On the other hand, the cross-talk between the niche components implies that an abnormal cell population may also redesign the microenvironment in its favor [14,17,18]; for instance, the experimental evidence highlights the role of non-hematopoietic BM stromal elements in leukemia initiation and progression [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%